2022
DOI: 10.3389/fneur.2022.1032738
|View full text |Cite
|
Sign up to set email alerts
|

The accumulation of muscle RING finger-1 in regenerating myofibers: Implications for muscle repair in immune-mediated necrotizing myopathy

Abstract: BackgroundMuscle RING finger-1 (MuRF-1) plays a key role in the degradation of skeletal muscle proteins. We hypothesize the involvement of MuRF-1 in immune-mediated necrotizing myopathy (IMNM).MethodsMuscle biopsies from patients with IMNM (n = 37) were analyzed and compared to biopsies from patients with dermatomyositis (DM, n = 13), dysferlinopathy (n = 9) and controls (n = 7) using immunostaining.ResultsMuRF-1 staining could be observed in IMNM, DM and dysferlinopathy biopsies, whereas the percentage of MuR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…Other studies have shown that increased expression of MuRF-1 after muscle damage can increase the ubiquitination process of damaged myofibrillar and sarcoplasmic proteins (Baehr et al, 2021;Yang et al, 2022), thus contributing to successful tissue repair and promoting faster recovery. However, it is hypothesized that the restricted affinity of proteins (MuRF-1 and titin) could affect the interactions between the contractile and structural properties of muscle fibers, the muscle regeneration process and contribute to a less resistant muscle.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Other studies have shown that increased expression of MuRF-1 after muscle damage can increase the ubiquitination process of damaged myofibrillar and sarcoplasmic proteins (Baehr et al, 2021;Yang et al, 2022), thus contributing to successful tissue repair and promoting faster recovery. However, it is hypothesized that the restricted affinity of proteins (MuRF-1 and titin) could affect the interactions between the contractile and structural properties of muscle fibers, the muscle regeneration process and contribute to a less resistant muscle.…”
Section: Discussionmentioning
confidence: 97%
“…MuRF-1, MuRF-2 and MuRF-3 proteins are a specific class of proteins expressed in striated and cardiac muscle tissues (Chen et al, 2012;Peris-Moreno et al, 2020). The MuRF-1 protein mediates a key role in the Ubiquitin Proteasome System (UPS), attaching ubiquitin polymers to deteriorated myofibrillar proteins after muscle damage (Centner et al, 2001;Yang et al, 2022). MuRF-1 is localized at the Z-and the M-line of the sarcomere, in which it has been found to interact and modulate the mechanical properties of titin (Baehr et al, 2021;Bodine et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also consider checking the antibodies in patients who present with chronic progression since such cases have been rarely described, particularly in patients with younger onset. 6 These patients may have already had or may undergo simultaneous genetic testing for muscular dystrophy.…”
Section: Hmgcr Imnmmentioning
confidence: 99%
“…However, cases with slow progression over 6 months to years have also been described, particularly in pediatric patients, resembling muscular dystrophy. [3][4][5][6] Serum creatine kinase (CK) is elevated, oftentimes more than five times the upper limit of normal on presentation and typically higher than is seen with other IIMs. 7 Antibodies may be present against 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR) or signal recognition peptide (SRP), or neither may be present (hereinafter referred to as seronegative).…”
mentioning
confidence: 99%